Perancangan Aplikasi Resepsionis Berbasis Web - Karmila, Mita; Sujadi, Harun (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
The Sindang District Office is a government agency that has responsibility for data processing in the Sindang District area. To support effectiveness, efficiency and productivity in an agency in improving service quality, including providing services to the community in the Sindang District area at the reception. To overcome this problem, it is necessary to solve the problem by using a web-based application system so that it can easily find data and search for data. The method used by researchers is a waterfall which consists of several stages, namely requirements, design, implementation, verification and maintenance that have been successfully created and have succeeded in storing community data into a system. Keywords: Receptionist, Web Based, Waterfall.